Characteristics of ICU and Operating Room Patients at Satellite Hospitals Study Program Anesthesiology and Intensive Care Faculty of Medicine Universitas Sumatera Utara - Primaputra Lubis, Andriamuri; Irina, Rr Sinta; Ginting, Ananta Septriandra (Talenta Publisher, 2023)
Characteristics patient of admission to the intensive care unit and operating room are needed for better team development and achievement competence. The purpose of this study was to describe the characteristics of critical patients in the intensive critical unit and operating room. This research method is quantitative with a descriptive design using secondary data. The data were obtained from the medical records of the ICU of the public hospitals in Sibolga City, Central Tapanuli Regency and Padangsidempuan City. The results of research in the ICU showed that the majority of critical patients were female (51.17%), aged 56-65 years (25.76%), primary diagnoses of disorders of the neurological system (24.36%), and the patient's prognosis moved to the emergency room. treated or referred (61.31%). The results of the study in the operating room found that the majority of the sexes were male (54.20%), the largest sample aged 56-65 years (31.52). The most common surgical procedures were surgery on the nervous system (42, 86). The prognosis of patients after surgery is that more patients are transferred to the ward or ICU (57.14%) However, further research is needed on other characteristics to provide a more comprehensive understanding.